2005
DOI: 10.1161/01.res.0000176022.74579.47
|View full text |Cite
|
Sign up to set email alerts
|

Optical Action Potential Upstroke Morphology Reveals Near-Surface Transmural Propagation Direction

Abstract: Abstract-The analysis of surface-activation patterns and measurements of conduction velocity in ventricular myocardium is complicated by the fact that the electrical wavefront has a complex 3D shape and can approach the heart surface at various angles. Recent theoretical studies suggest that the optical upstroke is sensitive to the subsurface orientation of the wavefront. Our goal here was to (1) establish the quantitative relationship between optical upstroke morphology and subsurface wavefront orientation us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
96
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(108 citation statements)
references
References 35 publications
10
96
2
Order By: Relevance
“…Figure 5c depicts a so-called V F Ã-map, where V F Ã is the fractional level at which the optical upstroke reaches a maximal derivative. As shown in previous studies [54,57,61], V F Ã can be used to infer the average subsurface wavefront orientation shown in figure 5d. The subsurface angle is positive for waves propagating away from the epircardial surface and negative for waves propagating towards the epicardium.…”
Section: Optical Mappingmentioning
confidence: 81%
See 1 more Smart Citation
“…Figure 5c depicts a so-called V F Ã-map, where V F Ã is the fractional level at which the optical upstroke reaches a maximal derivative. As shown in previous studies [54,57,61], V F Ã can be used to infer the average subsurface wavefront orientation shown in figure 5d. The subsurface angle is positive for waves propagating away from the epircardial surface and negative for waves propagating towards the epicardium.…”
Section: Optical Mappingmentioning
confidence: 81%
“…Signals from 1 mm deep contribute to the optical signal; longer wavelength light (near infrared) is less prone to scattering and absorption, and so novel near-infrared voltage-sensitive dyes [58 -60] with longer excitation wavelengths allow for imaging deeper layers in cardiac tissue [17]. These intramural components to the epi-fluorescence signal can be exploited to provide information about propagation direction within the heart wall [54,61]. The shape of the optically recorded action potential upstroke depends on the orientation of the wavefront: the optical upstroke is fastest near the top of the action potential for waves propagating towards the imaged surface, whereas the faster portion of the upstroke is located near the foot of the action potential when the wave propagates away from the imaged surface.…”
Section: Optical Mappingmentioning
confidence: 99%
“…These findings were validated with other electrical models (i.e. bidomain and Luo-Rudy) [17][18]. It would be very interesting to compare the solution of the Aliev and Panfilov model with the calculated transmembrane potential generated by the flux of photons during the process of illumination and emission.…”
Section: Discussion and Future Worksupporting
confidence: 56%
“…These APs had significantly lower amplitudes and two components of upstroke ( Figure 4B) which reflected activation of the deeper layers and scattered light signal from tissue outside of electroporated area ( Figure 4B). We could derive the transmural waveform orientation from the morphology of upstroke of optical AP ( Figure 2A in Online Data Supplement) using the algorithm proposed by Hyatt et al (32) We found increased transmural propagation after shock as a result of the wave front "diving" below the electroporation-induced conduction block and "resurfacing" after passing through the electroporated region (see maps of V max,%APA in Figure 3 and 4).…”
Section: Mechanism Of Electroporation-induced Conduction Blockmentioning
confidence: 97%